2017
DOI: 10.22159/ajpcr.2017.v10i8.18861
|View full text |Cite
|
Sign up to set email alerts
|

Brine Shrimp Teratogenic Screening Test on Some Selected Plants

Abstract: Objectives: The aims of this research were to analyze teratogenic properties on some selected plants which often used for woman’s health were pomegranate (Punica granatum L.) pericarp, coriander (Coriandrum sativum L.) seeds, liman (Elephantopus scaber L.) leaves, fennel (Foeniculum vulgare M.) seeds, and kaempferia (Kaempferia galanga L.) rhizomes using brine shrimp teratogenic screening test (BSTST) method.Methods: Artemia cysts were hatched into first stage nauplii then taken and put into seawater medium wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Clinical observation, body weight, ocular examination, food consumption, and organ weight all had no statistically significant value. Differences from the control were seen in serum chemistry and hematology measures, but there was no evidence of a harmful effect on biological variation as presented by Lestari, Soemardji and Fidrianny [43], Patel, Dadhaniya, Hingorani and Soni [44].…”
Section: Discussionmentioning
confidence: 74%
“…Clinical observation, body weight, ocular examination, food consumption, and organ weight all had no statistically significant value. Differences from the control were seen in serum chemistry and hematology measures, but there was no evidence of a harmful effect on biological variation as presented by Lestari, Soemardji and Fidrianny [43], Patel, Dadhaniya, Hingorani and Soni [44].…”
Section: Discussionmentioning
confidence: 74%
“…The reproduction performance of rat's mother which was given by liman leaves extract at the 11 th day was similar to teratogenicity screening result using brine shrimp test (BST). The result of BST screening showed that high concentration of liman leaves extract (6 mg/ml) caused higher percentage of dead nauplii than the other concentrations, while developmental disorder was mostly found at low concentration (1.5 mg/ml) [18].…”
Section: Discussionmentioning
confidence: 96%
“…Experiments were conducted along with control (vehicle-treated), different concentrations (100-1000 µg/ml) of the substances in a set of three tubes per dose. Based on the percent mortality, the LDR 50R of the test compound was determined using the probit scale [15].…”
Section: Acute Cytotoxic By Brine Shrimp Lethality Assaymentioning
confidence: 99%